Ichthyofaunal survey of stretches of the Guariba and Rooselvelt Rivers, in Guariba State Park and Guariba Extractive Reserve, Madeira River basin, Amazonas, Brazil - Pedroza, Wellington Silva; Ribeiro, Frank Raynner Vasconcelos; Teixeira, Túlio Franco; Ohara, Willian Massaharu; Py-daniel, Lúcia Rapp (Check List, 2012)
The fishes presented herein were collected in small streams, in channel of lagoons and in the main channel of the Guariba River, as well as in one tributary of the right bank of the Roosevelt River, both clear-water tributaries of Aripuanã River, Madeira River basin. Field work was carried out in November 2008, during the low water season. Sampling resulted in 3924 specimens belonging to 160 species distributed in 34 families, and seven orders. Eight species are recognized as new, two of which were recently described. This study represents the first fish survey for the region and will certainly provide valuable information for future studies and maintenance of the poorly known fish diversity of these two conservation areas. © 2012 Check List and Authors.
Keywords: Pisces